MAGNETIC AND STRUCTURAL STUDIES OF FeSi MULTILAYERS IRRADIATED BY ARGON IONS - Setyo Purwanto; I. Sakamoto; M. Koike; H. Tanoue; S. Honda (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2005)
MAGNETIC AND STRUCTURAL STUDIES OF FeSi MULTILAYERS IRRADIATED BY ARGON IONS. We prepared Fe/Si multilayers (MLs) by helicon plasma sputtering to investigate the antiferromagnetic couplings (AFC) between Fe layers sandwiched by Si spacers. [Fe (2nm)/Si (1.5nm)]30 MLs showed the ferromagnetic couplings (FC). The ion irradiation by 400 keV Ar ions was performed to [Fe (2nm)/Si (1.5nm)]30 MLs using AIST 400 keV ion implanter. The magnetic and structural properties were investigated by Vibrating Sample Magnetometer (VSM) and Conversion Electron Mössbauer Spectroscopy (CEMS). The value of saturation magnetization in as-deposited [Fe (2nm)/Si (1.5nm)]30 MLs is smaller than that of bulk α-Fe (1700 emu at RT). This decrease of saturation magnetization implies an atomic mixing in the interface region. The values of saturation magnetization decrease with increasing Ar ion dose. The CEMS spectrum of [Fe (2nm)/Si (1.5nm)]30 MLs shows the doublet peaks overlapped with broad sextet peaks. The doublet peaks correspond to nonmagnetic Fe1-xSix phases formed in the interface region. On the other hand, the distribution of hyperfine fields (Hhf) was estimated from broad sextet peaks and smaller values of Hhf correspond to ferromagnetic Fe1-xSix phases. The amounts of nonmagnetic Fe1-xSix phases in CEMS spectra seem not to change with increasing Ar ion dose but the values of Hhf decrease with increasing Ar ion dose. These results indicate the peculiar atomic mixing by Ar ion irradiation in the interface region.